COMPUTATIONAL SIMULATION AND WENO METHOD EVALUATION OF DIRECT FORCE CHARACTERISTICS - Taylor, Michael (Ayden International Journal of Basic and Applied Sciences, 2024)
In the pursuit of precision-guided weapons, the direct force active control technology, particularly in direct gas composite, has emerged as a critical and promising avenue. This technology empowers aircraft with the ability to execute large motor and agile flights, filling the void left by conventional aerodynamic forces and boosting maneuverability and targeting accuracy. To achieve this, the utilization of thrust vectoring or lateral jets is pivotal to generate lateral forces for auxiliary control. The employment of lateral jets presents several noteworthy advantages over traditional air rudder control: Swift control response, enhancing the capacity for kinetic energybased target interception. Mitigation of pneumatic heating's ablation effect on components during hypersonic flight. Improved control efficiency in low-speed, low-density conditions when aerodynamic steering surfaces falter. Effective lateral force provision during the final approach phase, especially when the main engine is no longer operational.